Challenges Experienced by Rural Women in India Living With AIDS and Implications for the Delivery of HIV/AIDS Care - Adeline Nyamathi; Sanjeev Sinha; Kalyan K. Ganguly; Ravi Raj William; Anisa Heravian; Padma Ramakrishnan; Barbara Greengold; Maria L. Ekstrand; Pantangi Venkata Rama Rao (2011)
Researchers explored the barriers to AIDS care for rural women living with AIDS, and they investigated alternative delivery models to increase the women's adherence to antiretroviral therapy (ART). Community-based participatory research focus groups were conducted by the researchers with a convenience sample of 39 women living with AIDS from a primary health center (PHC) near Chennai, India, and with nurses, physicians, and Accredited Social Health Activists (Ashas), who are lay health care workers. The most prevalent barriers expressed by the women were sickness-related, psychological, financial issues with childcare, and distance, or transportation to the site. Women living with AIDS reviewed Ashas favorably.